Styrene finishing stills at Dow Chemical Company - Dow Chemical Company (1952)
Close-up view of the underside of the styrene finishing stills at a Dow Chemical Company plant in Midland, Michigan. An organic compound derived from benzene, styrene is a precursor to polystyrene and was popularized in the 1940's as a feedstock for synthetic rubber.
Keywords: Distillation apparatus; Industries; Dow Chemical Company; Styrene industry; Monomers; Styrene